Abiraterone for Prostate Cancer Not Previously Treated with Hormone Therapy - James, Nicholas D; de Bono, Johann S; Spears, Melissa R; Clarke, Noel W; Mason, Malcolm D; Dearnaley, David P; Ritchie, Alastair W.S; Amos, Claire L; Gilson, Clare; Jones, Rob J; Matheson, David; Millman, Robin; et al. (The New England journal of medicine, 2017)
The addition of abiraterone and prednisolone to standard androgen-deprivation therapy as the first treatment for patients with locally advanced or metastatic prostate cancer improved overall and failure-free survival, with a small increase in high-grade toxic effects.